THU0422 CALCIUM PYROPHOSPHATE CRYSTAL DEPOSITION WITHIN TOPHUS LOBULE: A FREQUENT ASSOCIATION OBSERVED IN LONG-TIME COURSE TOPHI. (2nd June 2020) - Ea, H. K.; Olivier, O.; Pham, N. N.; Frochot, V.; Bazin, D.; Marty, C.; Ostertag, A.; Laredo, J. D.; Richette, P.; Nguyen, Q. D.; Bardin, T.
Abstract : Background: Calcium pyrophosphate (CPP) crystals and monosodium urate (MSU) crystals are frequently found in the same synovial fluids of gouty patients suggesting an interaction in crystal formation and deposition. This association has never been reported in tophus. Objectives: we aimed to describe the prevalence of CPP crystal deposition in tophus and to determine the associated risk factors. Methods: 22 tophi consecutively harvested were fixed in 4% paraformaldehyde and embedded in paraffin. 5-µm thick sections were analyzed by compensated polarized microscopy (CPM) after hematoxylin and eosin staining. Characterization of CPP crystals were performed by scan electronic microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. Clinical characteristics were compared between patients having tophus with CPP deposition and patients having tophus without CPP crystals. Results: All tophi appeared multi-lobulated depositions of MSU crystals separated by fibrous tissue and surrounded by a foreign giant cell reaction. CPP crystals were identified in few lobules of 5 tophi (22.7%) harvested from 3 great toes, 1 elbow bursa and 1 finger of 5 patients. CPP crystals formed aggregate deposition within the lobule of MSU crystals. Both monoclinic and triclinic CPP crystal phases were identified by CPM, SEM and FTIR. Tophi were harvested from 22 male gouty patients with a mean age of 50.8 (28-66) years and a mean BMI of 24.2 kg/m2 (18.9-29.4). Mean serum urate level (SUL) was 499 ± 107 µmol/L. 59% of patients had chronic renal disease stage 2 or 3, 40.9% dyslipidemia, 22.7% type 2 diabetes mellitus, 13.6% hypertension and 50% obesity. Patients with tophi containing CPP deposition were older (61.2 [56-66] vs 47.8 [28-64] years, p=0.009) and had a longer gout duration (19 [10-31] vs 9 [3-20] years, p= 0.007) and tophus duration (11.4 [8-16] vs 4.5 [1-9] years, p< 0.0001) than patients with tophi alone. Tophi did not display calcification on radiographies performed before surgery. However, the density of tophi containing CPP crystal deposition was higher than the density of tophi without CPP crystals (51 [25-100] vs 21.5% [0-40], p=0.009). The proportion of bone erosion and gout arthropathy was similar between the two groups. Similarly, no difference was observed for SUL (467 ± 43 vs 509 ± 109 µmol/L), estimated glomerular filtration rate (76.6 ± 11.9 vs 74.9 ± 15.7 ml/min/1.73m2) and prevalence of comorbidities. Interestingly, no calcification was detected on knee and wrist radiographies of patients with tophi containing CPP deposition. Conclusion: These results reported for the first time, in a small sample size, that CPP crystal deposition occurred within tophus lobules. They suggested that long-time course tophi might act as a facilitating agent of CPP nucleation. This hypothesis needs specific confirmation studies Disclosure of Interests: None declared